Form of Criminal Liability for Persons of Mayantara Criminal Actions - Imam Makhali (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2022)
Indonesia is a country involved in the use and utilization of information technology, which is proven by a large number of internet users, along with advances in information technology in communication media that have changed people's behavior in global civilization. This technology causes world relations to become closer without borders and boundaries. Along with the development of technology, the form and mode of crime also developed. In Indonesian Criminal Law, for perpetrators of cyber crimes or usually called “mayantara” crimes, they are burdened with criminal responsibility like criminal acts regulated in the Criminal Code. accountability criminal for criminals. The form of criminal responsibility for perpetrators in criminal law, especially cybercrime which has been adopted by Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions is regulated in 9 articles, from article 27 to is doctrine of identification. This can be proven by the acceptance of forms of criminal liability including corporations ( corporate criminal liability ) as cyber crime preperators.